Clinical efficacy and cardiorespiratory effects of intramuscular administration of alfaxalone alone or in combination with dexmedetomidine in cats. (13th October 2015) - Rodrigo‐Mocholí, Diego; Belda, Eliseo; Bosmans, Tim; Laredo, Francisco G.
Abstract: Objective: To investigate the sedative, anaesthetic and cardiorespiratory effects of intramuscular (IM) administration of alfaxalone alone or in combination with dexmedetomidine in cats. Study design: Blinded, randomized crossover study with a washout period of 15 days. Animals: Seven adult cats, weighing 3.5 ± 0.7 kg. Methods: Cats were assigned randomly to each of three treatments: A5 (alfaxalone 5 mg kg −1 ), D20 A5 (dexmedetomidine 20 μg kg −1 and alfaxalone 5 mg kg −1 ) and D40 A5 (dexmedetomidine 40 μg kg −1 and alfaxalone 5 mg kg −1 ). Drugs were administered IM into the epaxial muscles. Sedation or anaesthesia scores were evaluated by a modified numerical rating scale. Times to extubation, head‐lift, sternal recumbency and standing were recorded. Heart and respiratory rates, systolic arterial pressure, arterial oxygen saturation of haemoglobin, end‐tidal carbon dioxide tension and rectal temperature were measured at 5, 10, 15, 20, 30, 45, 60, 90, 120 and 150 minutes after drug administration. Adverse events were recorded. Data were analysed by one‐wayanova with Tukey's post‐hoc test for parametric values and, for non‐normally distributed parameters, a Kruskal–Wallis test and Mann–Whitney U ‐test for two independent samples ( p < 0.05). Results: Sedation scores were significantly different among the treatments. Cats in A5 were deeply sedated, whereas cats administered dexmedetomidine were anaesthetized. The onset of action and the duration of anaesthesia were related to the dose of dexmedetomidine. Cardiorespiratory parameters remained stable in the A5 group. Lower heart rates, higher systolic blood pressures and occasional low pulse oximetry readings were observed in the dexmedetomidine groups. A limited number of adverse events (hyperkinesia, emesis) occurred during recovery. Conclusions and clinical relevance: Alfaxalone administered IM induced sedation in cats. The addition of dexmedetomidine to alfaxalone induced general anaesthesia with a mild decrease in the heart rate and arterial oxygen saturation of haemoglobin.